COST ASPECTS OF RENEWAL IN ASSET MANAGEMENT AND FINANCIAL REGULATION - Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study examines the cost aspects of asset depreciation and financial regulations that affect the financial management and reporting of entities. Using a literature review method, this study analyses the classification of depreciation costs, their impact on asset performance, and how financial regulations govern the management of these costs to comply with applicable accounting standards and fiscal policies. The results of the study indicate that effective cost management must be supported by compliance with financial regulations to ensure transparency, accountability, and asset sustainability. This study provides an important theoretical basis for policymakers and practitioners in designing efficient and regulatory-compliant asset management strategies.